Synergistic effect of NS co-doped TiO2 adsorbent for removal of cationic dyes. Issue 4 (August 2021) - Rashid, Ruhma; Shafiq, Iqrash; Iqbal, Muhammad Javid; Shabir, Maira; Akhter, Parveen; Hamayun, Muhammad Haris; Ahmed, Ashfaq; Hussain, Murid
Abstract: Removal of dyes from wastewater specially from textile effluents has been given considerable attention in the last few decades, not only for their health issues but also potential toxicity. Over the former few eras, TiO2 based adsorbents have drawn worldwide attention as an efficient adsorbent for wastewater treatment due to their versatile physio-chemical characteristics. This paper outlined the synthesis of nitrogen and sulfur co-doped TiO2 (NS/TiO2 ) nanostructures and highlighted their applications in the removal of dyes, including methylene blue (MB), methyl orange (MO) and methyl red (MR). The nanostructures were characterized by using scanning electron microscopy (SEM), X-Ray Diffraction pattern (XRD), Brunauer-Emmett-Teller measurements (BET), Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy. Batch experiments of adsorption were carried out by varying solution pH, adsorbent dose, initial dye concentration and contact time. The results revealed that dye adsorption capacity increased with increased adsorbent dosage up to 0.06 g, solution pH from 1 to 14 and contact time from 20 to 140 min. However, the adsorption capacity decreases with increase in the initial dye concentration. The experimental data were analyzed by the Langmuir and Freundlich adsorption isotherms. NS/TiO2 adsorbent exhibited a high affinity towards organic dyes due to the heterogeneous sorption capacity. The NS/TiO2 adsorbent showed 99.4% removal efficiency for MB, 98% for MO and 96% for MR. The adsorbent could be regenerated in an acidic medium for MB and a basic medium for MO and MR with good activity, even after three repeated cycles. Graphical Abstract: ga1 Highlights: NS/TiO2 was synthesized for efficient adsorption of cationic dye from wastewater. Parametric study of as-synthesized NS co-doped TiO2 for adsorption performance. The heterogeneous adsorption surface of NS/TiO2 was verified by Freundlich isotherm. The possible adsorption mechanism was postulated. The adsorbent was regenerated and effective for at least three cycles.